A new detection method for the K variant of butyrylcholinesterase based on PCR primer introduced restriction analysis (PCR-PIRA). Issue 7 (July 1994) - Shibuta, K; Abe, M; Suzuki, T
Abstract : The K variant of human butyrylcholinesterase is caused by a G/A transition in the butyrylcholinesterase gene, which neither creates nor destroys any restriction site. In an attempt to detect the K variant both simply and rapidly, we developed a two step method of "PCR primer introduced restriction analysis" (PCR-PIRA). The first step was used to introduce a new Fun4HI site into the normal allele for a screening test, while the second step was performed to create a new MaeIII site on the variant allele for a specific test. This method thus enabled us to distinguish clearly the K variant from the normal allele, and also showed that the frequency of the K variant allele is 0.164 in the Japanese population.